Predictors of Delayed Defervescence in Scrub Typhus: A Retrospective Cohort Analysis - Sadia Tamanna; Dong-Min Kim; Choon-Mee Kim; You-Mi Lee; Da Young Kim; Jun-Won Seo; Na-Ra Yun (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Scrub typhus, caused by Orientia tsutsugamushi , is a mite-borne febrile illness endemic to the Asia-Pacific region. Although most patients respond promptly to appropriate antibiotic therapy, a subset exhibits delayed defervescence, the clinical significance and predictors of which remain insufficiently understood. In the present study, the authors aimed to identify clinical, laboratory, and radiological factors associated with delayed defervescence in patients with scrub typhus. In this retrospective cohort study, scrub typhus patients who were hospitalized at Chosun University Hospital, Gwangju, South Korea, between November 2005 and November 2008 were assessed. Demographic characteristics, clinical manifestations, laboratory values, and radiological findings were compared. Multivariate logistic regression was used to identify independent predictors. During the study period, 413 patients were recorded initially. Among 160 confirmed scrub typhus patients, 22 (13.8%) experienced delayed defervescence. Compared with patients with early defervescence, those with delayed defervescence had significantly lower hemoglobin levels ( P = 0.045), higher rates of anemia ( P = 0.006) and leukocytosis ( P = 0.017), and elevated C-reactive protein levels ( P = 0.034). Pneumonia was also more common in the delayed group. In multivariate logistic regression analysis, anemia (odds ratio [OR]: 2.79; 95% CI: 1.00–7.79) and pneumonia (OR: 2.86; 95% CI: 1.07–7.59) were the strongest independent predictors of delayed defervescence. Delayed defervescence may reflect ongoing systemic inflammation and greater disease severity. Pneumonia and anemia could help identify patients at risk of a more severe clinical course or complications despite appropriate treatment, underscoring the importance of close monitoring.